A new furanoxanthone from the stem bark of Calophyllum inophyllum - Ee, Gwendoline Cheng Lian; Mah, Siau Hui; Rahmani, Mawardi; Yap, Taufiq Yun Hin; Teh, Soek Sin; Lim, Yang Mooi (Taylor & Francis, 2011)
The stem bark extracts of Calophyllum inophyllum furnished one new furanoxanthone, inophinnin (1), in addition to inophyllin A (2), macluraxanthone (3), pyranojacareubin (4), 4-hydroxyxanthone, friedelin, stigmasterol, and betulinic acid. The structures of these compounds were determined by spectroscopic analysis of 1D and 2D NMR spectral data (1H, 13C, DEPT, COSY, HMQC, and HMBC) while EI-MS gave the molecular mass. The new xanthone, inophinnin (1), exhibited some anti-inflammatory activity in nitric oxide assay.